STYK1 promotes Warburg effect through PI3K/AKT signaling and predicts a poor prognosis in nasopharyngeal carcinoma - Yunfei Zhao; Ling Yang; Jiao He; Huai Yang (Tumor Biology)
STYK1 (Serine/threonine/tyrosine kinase 1), a member of the receptor tyrosine kinase family, exhibits tumorigenicity in many types of cancers. Our study reveals the important role played by STYK1 in nasopharyngeal carcinoma. STYK1 is upregulated in nasopharyngeal carcinoma tissues compared with para-carcinoma. Knockdown of STYK1 inhibits nasopharyngeal carcinoma cell proliferation, migration, and invasion, while ectopic STYK1 expression significantly promoted cell proliferation, migration, and invasion abilities. In addition, we provided lines of evidence supporting the critical role of STYK1 in the regulation of glycolysis via activation of phosphoinositide 3-kinase/AKT pathway. Survival analysis reveals that STYK1 level is an independent prognostic factor for nasopharyngeal carcinoma patients. Our results indicate that STYK1 is a promising therapeutic target in nasopharyngeal carcinoma.